BUDIDAYA JAMUR PERUSAK KAYU IV. KULTUR JAMUR PADA SUBSTRAT SERBUK GERGAJI YANG DIPERKAYA - Sihati Suprapti; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Oyster mushroom (Pleuroius ostreatus) has been cultivated on five sawdust media of five wood species, i.e. durian (Durio zibethinus Murr.), jeungjing (Albizia falcataria (L.) Fosb.). manii (Maesopsis eminii Engl.), rubber (Hevea brasiliensis Muell. Arg.) and coconut (Cocos nucifera L.). The composition of the media was 100 % saw dust, 80 % sawdust + 20 % rice bran, 99.5 % sawdust + 0.5 % lime, 99 % sawdust + 0.5 % lime + 0.5 % trisuperphosphate (TSP), and 97.5 % sawdust + 0.5 % lime + 0.5 % TSP + 1.5 % gypsum. Each media was mixed with sufficient distilled water. The media was allowed to cool after autoclave sterilization before being inoculated with pure culture of the mushroom. The mature mushroom was harvested daily after the growth of fruiting body.The highest yield was obtained from Rubber wood (129.8 g per 600 g media). The beat composition was obtained from sawdust 80 % mixed with rice bran 20 % (103.17 g per 600 g media).The higher Biological efficiency during the four month observation were obtained from media containing sawdu1t 80 % mixed with rice bran 20 %, i.e. rubber (66.73 %), durian 148.15 %), coconut (28.12 %), and manii (22.38 %).